2021
DOI: 10.1063/5.0046073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anion identity on ion association and dynamics of sodium ions in non-aqueous glyme based electrolytes—OTf vs TFSI

Abstract: Sodium-based rechargeable battery technologies are being pursued as an alternative to lithium, in part due to the relative abundance of sodium compared to lithium. Despite their low dielectric constant, glyme-based electrolytes are particularly attractive for these sodium-based batteries due to their ability to chelate with the sodium ion and their high electrochemical stability. While the glyme chain length is a parameter that can be tuned to modify solvation properties, charge transport behavior, reactivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…The decrease in diffusion coefficients for ions and diglyme at higher concentration of NaPF 6 /diglyme can be attributed to the strong interaction of diglyme and sodium ions and higher viscosity in the concentrated electrolyte, which restricts the diffusive motion of ions. These results are consistent with the previous findings of Kumar and coworkers ,, where the authors showed that an increase in the concentration of the salt and the length of the glyme chain leads to reduced diffusion coefficients.…”
Section: Results and Discussionsupporting
confidence: 93%
“…The decrease in diffusion coefficients for ions and diglyme at higher concentration of NaPF 6 /diglyme can be attributed to the strong interaction of diglyme and sodium ions and higher viscosity in the concentrated electrolyte, which restricts the diffusive motion of ions. These results are consistent with the previous findings of Kumar and coworkers ,, where the authors showed that an increase in the concentration of the salt and the length of the glyme chain leads to reduced diffusion coefficients.…”
Section: Results and Discussionsupporting
confidence: 93%
“…The ionic transport and corresponding mechanisms are intensively dependent on the electrolyte structures because the cation− solvent, cation−anion, and plausible anion−solvent interactions determine the exchanging behaviors of Li + -coordinated species. 397,398 Weak and strong cation−solvent interactions are beneficial to vehicular and structural diffusions, respectively. Considering the high correlation between solvation structures and ionic transport, factors relevant to solvation structures also influence ionic transport.…”
Section: Ionic Transportmentioning
confidence: 99%
“…However, the larger ionic size and greater atomic mass of Na vis-a-vis Li severely restrict the energy density of Na-based systems. 3 An important research area for enhancing the performance of NIBs involves electrolyte design, which governs the overall performance of the device with its properties such as ionic conductivity, electronic resistance, chemical/electrochemical stability, thickness, etc. 4 A large variety of liquid/solid/ polymeric electrolytes has been employed in NIBs, which have different merits and demerits.…”
Section: Introductionmentioning
confidence: 99%
“…5−7 In recent years, etherbased solvents such as glymes have gained much focus. 3 Glymes are basically polar aprotic saturated polyethers with a chemical formula of CH 3 (CH 2 CH 2 O) n OCH 3 [n = 1, 2, 3, etc. ], e.g., monoglyme (G1), diglyme (G2), triglyme (G3), etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation